Seductive Details and Expository Text Structures: an Experimental Study via Keyword Extraction - Trushchelev, Pavel (Bulletin of Yerevan University H: Russian Philology, 2025)
Seductive details are intriguing yet extraneous pieces of information in expository texts. Understanding their impact on text comprehension is essential for effective expository reading. The aim of the study was to examine the processing of expository texts that contain seductive details of varying significance. The significance of seductive details was evaluated based on their textual function in constructing referential and thematic structures. The study utilised three expository texts from Russian geography textbooks intended for seventh-grade students. The texts varied in significance and quantity of the seductive details included. A total of 40 seventh-grade students and 24 university students participated in the experiment, providing a diverse perspective on text comprehension. The study employed a keyword extraction method. The participants read the texts and extracted words they considered most important in terms of content. In total, 64 keyword sets were collected (n = 2,147 tokens); they presented the range of key concepts identified by participants. The participants successfully identified the main text ideas. The school students used a more concrete mode of text processing and extracted more specific keywords. The significance of the keywords depended on (i) their frequency in the text, (ii) their distribution across text sections, reflecting their impact on the elaboration, and (iii) the presence of contrast markers. The textual function of seductive details influenced the significance of the keywords extracted from them by the participants. Seductive details were interpreted by participants not only as sources of information but also as signals of significant text ideas.
Keywords: expository text; seductive details; keywords; text comprehension; text structures; keyword extraction